SP4.2.5 Did COVID-19 change the way we treat appendicitis?. (28th October 2021) - Hurt, Libor; Mowbray, Nicholas; Powell-Chandler, Anna; Reeves, Nicola; Chandler, Susan; Walters, Emyr
Abstract: Intro/aims: In repsonse to the COVID-19 pandemic, the United Kingdom (UK) commenced a national lockdown in March 2020. Initial guidance advocated the avoidance of aerosol generating procedures and hence we hypothesised there would be a decrease in the use of surgery to treat acute appendicitis. Methods: A prospective audit was undertaken across 4 hospitals in South Wales, UK, during April 2020. Patients over 18 years of age with suspected or confirmed appendicitis were identified and data was collected including their history, radiological findings, management, and re-admission. Comparison was made with theatre and radiological data from April 2018 and 2019. Results: A total of 254 patients were treated over the 3-year period; 95 patients in 2018, 95 in 2019 and 64 in 2020. During the lockdown, the use of Computed Tomography (CT) increased from 36.3% to 85.9% (p < 0.001). An antibiotic only approach to treat appendicits rose from 6.2% to 40.6% (p < 0.001). Four patients in the lockdown cohort failed the conservative approach and required an appendicectomy. The overall rate of laparoscopic appendicectomy was reduced from 85.3% to 17.2% (p < 0.001). A malignancy was identified in 3% of cases. Conclusions: Whilst less patients presented with acute appendicitis compared to previous years, there was still a significant reduction in the operation rate. The data aligns with the literature confirming the antibiotic-only approach to be safe with a low failure rate. It is essential however that patients are fully consented for this approach including the risk of a missed malignancy.